'This object really touched me': using Le Guin's carrier bag theory to explore stories of the self on an international professional doctorate development programme. Issue 2 (4th May 2022) - O'Connor, Jane; Chun, Cao; Hai, Pham Thi Thanh; Wheatcroft, Louise; Wiyarsi, Antuni; Huy, Nguyen Hoang Doan; Nguyen, Thai-Huu; Lieu, Le Thi Thu; Huynh, Tan; Hanh, Luu
ABSTRACT: This piece reflects on an innovative introductory workshop for an international professional doctorate development project based on Ursula Le Guin's 'Carrier Bag Theory of Fiction'. In the session academic supervisors from four participating countries shared stories about their own experiences of doing a doctorate using a bag of everyday objects which reminded them of their time as students. The exercise gave the group an opportunity to begin to get to know each other and to appreciate the complexity and challenge that completing a doctorate whilst working and balancing other personal and family responsibilities entails. Drawing on humanist pedagogical approaches which value the inner world of the learner and taking inspiration from previous arts based approaches to identity work for education students and practitioners the piece argues for the importance of making space for story-telling about the self from the outset of professional doctorate programmes.